Biodegradation of three-layer laminate films based on gelatin under indoor soil conditions - Martucci, Josefa Fabiana (2009)
Three-layer gelatin ﬁlms, composed of sodium montmorillonite (MMt) – plasticized gelatin (Ge-5MMt) (inner layer) and dialdehyde starch (DAS) – cross-linked and plasticized gelatin ﬁlms (Ge-10DAS) (outer layers), obtained by heat-compression molding, were submitted to degradation under indoor soil burial conditions for 14 days. Biodegradation of multilayer ﬁlm as well as individual components and control gelatin ﬁlms was evaluated by monitoring water absorption and weight loss. It was established that technological treatments performed on gelatin, such as cross-linking, compounding with clay and heatcompression molding have a major impact on the biodegradation rate and extent. The possible reasons are discussed. Weight loss results revealed that the susceptibility to microbial attack during soil burial varied in the order: Ge-10DAS < multilayer < Ge-5MMt < gelatin control ﬁlm. The intermediate behaviour of the multilayer was associated with the presence of hydrogen-bonding interactions between layers, induced by processing. Scanning electron microscopy revealed that the multilayer was preferentially biodegraded by ﬁlamentous microorganisms and even larvae in the later stages of the process. The presence of holes and pits on the multilayer surface was more likely attributed to the preferential removal of glycerol and DAS as shown by thermogravimetric analysis